2012
DOI: 10.1016/j.jff.2011.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of gastrointestinal transit in rats fed dietary fibres differing in their susceptibility to large intestine fermentation

Abstract: Non-digestible carbohydratesShort-chain fatty acids Titanium dioxide Transit time A B S T R A C TThe rate and extent of in situ digesta transit after ingestion of diets containing dietary fibres differing in their susceptibility to large intestine fermentation were investigated. One hundred and twenty rats were fed diets containing 7.5% cellulose, inulin, potato fibre or maize starch for 3 days, then the same diets with titanium dioxide (TiO 2 ) for 3 days, followed by diets without TiO 2 for 2 days. In all di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Finely ground freeze‐dried faecal samples (100 mg) from each rat were used to measure the total faecal dietary fibre according to the method described by Paturi et al . (). The faecal samples were extracted twice with 80% ethanol (5 mL).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Finely ground freeze‐dried faecal samples (100 mg) from each rat were used to measure the total faecal dietary fibre according to the method described by Paturi et al . (). The faecal samples were extracted twice with 80% ethanol (5 mL).…”
Section: Methodsmentioning
confidence: 97%
“…Functional dietary fibres are constantly being developed by the food industry for use as ingredients in the manufacturing of food products to promote human health. We have investigated the fermentability of dietary fibres (inulin, potato fibre and maize starch) in the large intestine of rats and found that changes occur rapidly in the microbiota metabolic profile with higher levels of fermentation end products (organic acids) detected from day 4 onwards (Paturi et al ., ). A short‐term study conducted in humans also showed the ability of plant‐ and animal‐based diets to rapidly induce changes in gut microbiota composition and metabolic activity (David et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…A sample of finely ground feces (100 mg) from each rat was used to measure the total fecal dietary fiber according to the method described by Paturi and others (2012a)…”
Section: Methodsmentioning
confidence: 99%
“…Microcrystalline cellulose (Ceolus PH-102) was chosen as a control due to its non-fermentability, while inulin (Fibruline XL, degree of polymerisation >20) was selected as a fermentable fibre due to its high degree of fermentability in the large intestine (Paturi et al, 2012). In the present study, we investigated in newly weaned rats the very early influence of diets supplemented with either cellulose or inulin on colonic microbiota and fermentation end-products, and the resultant effects on mucin gene expression and morphology.…”
Section: Introductionmentioning
confidence: 99%